THE INFLUENCE OF SERVICE QUALITY TOWARDS TO CUSTOMER SATISFACTION (STUDY AT BPR PRISMA DANA MANADO) - Rompas, Pamela Christania; Lapian, Joyce; Tumiwa, Johan (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Service is the most important aspect in the banking sector. Customer satisfaction is one of the objectives of marketing activities in the marketing of goods and services for public consumption. A company can improve customer satisfaction by maximizing the care and services eliminate tedious and troublesome. This study aimed to examine the effect of Quality of Service to Customer Satisfaction, and to identify the variables that the dominant influence on customer satisfaction. The method used associative and data analysis techniques are Multiple Linear Regression to analyze the influence of assurance, empathy, reliability, response, as the reality of service quality variables for Customer Satisfaction. Results of Assurance, Empathy, Reliability, response, and the fact has a significant influence on customer satisfaction in BPR Prisma Dana Manado together. Guarantee a significant effect on customer satisfaction. Suggestions can be concluded that management BPR Prisma Manado Fund should consider Assurance, Empathy, Reliability, response, and the fact that a significant effect on customer satisfaction. Keywords : service quality, customer satisfaction, rural banks